Ответ:
В решении.
Объяснение:
у= -5,4 + х
1) -5,4 + (-0,5) = -(5,4 + 0,5) = -5,9;
2) -5,4 + 1,7 = -(5,4 - 1,7) = -3,7;
3) -5,4 + (-8,9) = - (5,4 + 8,9) = -14,3;
4) -5,4 + 10 = +(10 - 5,4) = 4,6;
5) -5,4 + 13,7 = +(13,7 - 5,4) = 8,3.
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
В решении.
Объяснение:
у= -5,4 + х
1) -5,4 + (-0,5) = -(5,4 + 0,5) = -5,9;
2) -5,4 + 1,7 = -(5,4 - 1,7) = -3,7;
3) -5,4 + (-8,9) = - (5,4 + 8,9) = -14,3;
4) -5,4 + 10 = +(10 - 5,4) = 4,6;
5) -5,4 + 13,7 = +(13,7 - 5,4) = 8,3.